Realism - The Ideological Chameleon (On TV Image “Realism”): Реализмот - идеолошкиот камелеон (за „реализмот“ на телевизиската слика) - Shikov, Viktor; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Viktor Shikov | Виктор Шиков Title (English): Realism - The Ideological Chameleon (On TV Image “Realism”) Title (Macedonian): Реализмот - идеолошкиот камелеон (за „реализмот“ на телевизиската слика) Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 131-141 Page Count: 10 Citation (English): Viktor Shikov, “Realism - The Ideological Chameleon (On TV Image ‘Realism’),” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002): 131-141. Citation (Macedonian): Виктор Шиков, „Реализмот - идеолошкиот камелеон (за „реализмот“ на телевизиската слика)“, Идентитети: списание за политика, род и култура, т. 1, бр. 2 (зима 2001): 131-141.